Rehabilitation and violence-related traumatic brain injury: A scoping review. - Samira Omar; Maria Jennifer Estrella; Muzna Ahmad; Angela Colantonio; Jessica Babineau; Vincy Chan (PLoS ONE)
Objectives There is a dearth of reviews exploring rehabilitation for violence-related traumatic brain injury (TBI) despite its increasing rates and distinct risk factors and outcomes. The aim of this scoping review is to determine the extent to which rehabilitation is available to and accessed by people who sustain TBI from interpersonal violence. Method Electronic databases (i.e., MEDLINE, Cochrane CENTRAL Register of Clinical Trials, CINAHL, APA PsycINFO, Criminal Justice Abstracts, Applied Social Sciences Index and Abstracts, and Proquest Nursing and Allied Health) and grey literature (i.e., relevant organizations' websites) were systematically searched for peer-reviewed articles and reports that met eligibility criteria. To be included, articles had to report primary findings on rehabilitation interventions that included individuals who sustained a TBI through interpersonal violence. Articles based on the military population were excluded. Data were synthesized through a descriptive numerical summary and qualitative content analysis. Results Fifty-two primary research articles and five grey literature reports were included. Most (77.2%) of these articles described rehabilitation interventions that addressed TBI sequalae without consideration for violence as a mechanism of injury, beyond reporting sample characteristics. Only thirteen articles (22.4%) considered violence-related TBI by investigating the rehabilitation profile (13.8%) or designing programs specifically for survivors of violence-related TBI (8.6%). There was limited attention to social determinants of health across all studies. Conclusion This is the first scoping review to our knowledge that explored the extent and nature of rehabilitation among persons who experience TBI through violence in civilian populations. Priorities for education, research, and practice are identified.